Idiopathic Myointimal Hyperplasia of the Mesenteric Veins: A Case Report and Scoping Review of Previously Reported Cases From Clinical Features to Treatment - Li, Hui; Shu, Hong; Zhang, Hong; Cui, Mingming; Gao, Yuying; Tian, Feng (Frontiers in Medicine, 2022)
Idiopathic myointimal hyperplasia of the mesenteric veins (IMHMV) is a rare and poorly understood disease. It is characterized by nonthrombotic and non-inflammatory occlusion of the mesenteric veins secondary to intimal smooth muscle hyperplasia. The etiology of IMHMV is unknown, and the clinical presentations of IMHMV include abdominal pain, bloody diarrhea, and weight loss. IMHMV is commonly mistaken for inflammatory bowel disease because of the similarity in symptoms and endoscopic findings. Herein, we report the case of a 64-year-old man with IMHMV and present an overview of all reported cases of IMHMV. In this review, we analyzed 45 cases to summarize the etiology, clinical manifestations, and diagnosis of IMHMV and hope to raise clinicians’ awareness of this entity.